Community Service in Winda Songket Riau: Implementation of Sustainopreneurship and Women's Empowerment: Pengabdian Kepada Masyarakat di Winda Songket Riau: Penerapan Sustainopreneurship dan Pemberdayaan Perempuan - Nasien, Dewi; Adiya, M. Hasmil; Siddik, M.; Suroyo, Suroyo; Mukhsin, Mukhsin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Community Service Activity (PkM) at Winda Songket, Riau, focuses on efforts to preserve the cultural heritage of songket weaving as part of Riau Malay culture, as well as improving the welfare of women through the application of a sustainopreneurship model. This program integrates ecological, economic, and social concepts to increase added value in the production of traditional Riau songket cloth. In addition, this program also emphasizes the importance of women's roles in maintaining and developing the songket business, thereby improving their economic welfare. This service involves socialization, training, and mentoring for songket craftsmen, hoping to encouragethem to adopt innovations in sustainable business models